Empirical Study of Environmental, Social & Governance (ESG) on the Stock Returns of Mining Companies With Profitability as an Intervening Variable Listed on the Indonesia Stock Exchange for the Period 2018-2023? - Ardhiati Octaviani; Hari Gursida; Yohanes Indrayono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of ESG on the stock returns of mining companies listed on the Indonesia Stock Exchange, as well as to assess whether profitability (ROA) plays a mediating role in that relationship. This study was conducted using a quantitative approach and employed panel data regression analysis on 16 companies over six years of observation (2018–2023), with a total of 96 observation data points. The model used is the Random Effect Model with heteroscedasticity correction through the EGLS method. The findings indicate that ESG disclosures, whether environmental, social, or governance, do not affect profitability and stock returns. Profitability (ROA) has a positive effect on stock returns, but it does not mediate the impact of ESG on those returns. This indicates that investors in the mining industry still prioritize conventional financial indicators over sustainability information in the investment decision-making process. Therefore, it is important for companies to enhance the relevance and integration of ESG into their business strategies in order to make a tangible contribution to market value. This research also opens up space for the exploration of other moderating factors that may strengthen the relationship between ESG and financial performance.